A DSGE model for a SOE with systematic interest and foreign exchange policies in which policymakers exploit the risk premium for stabilization purposes - Guillermo J. Escudé (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
This paper builds a DSGE model for a small open economy (SOE) in which the central bank intervenes the domestic currency bond and FX markets using two policy rules: a Taylor-type rule and a rule that determines the rate of nominal depreciation. The 2 'corner' regimes, in which only one policy rule is used, are particular cases. The model is calibrated and implemented in Dynare for simple and optimal simple policy rules, and optimal policy under commitment. Numerical losses are obtained for ad-hoc loss functions for different sets of central bank preferences. The results show that the losses are lower when both policy rules are used. This is due to the central bank's enhanced ability, when it uses the two policy rules, to influence private capital flows through the effects of its actions on the endogenous risk premium in the risk-adjusted uncovered interest parity equation.
Keywords: E58; F41; O24; 330; DSGE models; small open economy; exchange rate policy; optimal policy; Dynamisches Gleichgewicht; Kleine offene Volkswirtschaft; Wechselkurspolitik; Regelbindung; Theorie